Fresno County Bar Association and American Civil Liberties Union Celebrate the Constitution at Fresno City College - Watkins, Howard::::::::: (1988)
Ruth Gadebusch at lectern; Bill Tamayo from American Civil Liberties Union of Northern California and Howard Watkins at panel table